Analisis Kontrak Bisnis dalam Jual Beli Perdagangan Ekspor Muebel di Jepara - Muhammad Bayazid Albar; Romi Faslah (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
This study examines the legal aspects of business contracts in trade transactions, using a case study of furniture export contracts in Jepara. The focus of the study is on the clarity of contract clauses governing the obligations and responsibilities of the parties, as well as the resolution of disputes arising from breach of contract. The research method employs an empirical approach, analyzing primary and secondary legal materials. The results of the study indicate that a good export contract must meet the requirements of a valid agreement according to the Civil Code and regulate in detail the rights and obligations of the parties to avoid disputes. Dispute resolution can be carried out through arbitration mechanisms such as BANI. This study contributes to the understanding of the importance of clear and comprehensive business contracts in international trade.